Changes in wood production of Picea abies and Pinus sylvestris under a warmer climate: comparison of field measurements and results of a mathematical model. - Beuker, Egbert; Kolström, Marja; Kellomäki, Seppo (The Finnish Society of Forest Science and The Finnish Forest Research Institute, 2009)
Part I Climate Change To project the changes in wood production of Norway spruce Picea abies (L.) Karst. and Scots pine Pinus sylvestris L. in Finland as a result of climate change, two separate studies were made. The first study, at the Faculty of Forestry, University of Joensuu, based its projections on mathematical models; the second one, at the Finnish Forest Research Institute, based projections on measurements of wood production in two series of aged provenance experiments. The results of the two studies were similar for both species: after a 4 °C increase of the annual mean temperature a drastic increase in wood production in northern Finland, but little effect, or even some decrease in the southern part of the country. However, the assumptions used in the two studies differed. One important difference was that in the models the temperature is assumed to be increasing gradually over the years; whereas in the provenance experiments, climate changed immediately when the seedlings were transferred to the planting sites. Another problem with the provenance experiments is that when material is moved in a north-south direction in Finland, not only temperature but also photoperiod changes markedly. To compare these two studies, site factors (e.g. soil type, temperature, precipitation) and silvicultural factors (e.g. plant spacing, survival, time of thinning, thinning intensity) from the provenance experiments were included as variables in the mathematical models.